P-delta effects on short-period systems subjected to earthquake excitation. (1st March 2022) - De Francesco, Giovanni; Sullivan, Timothy J.
Abstract: Short period structures are commonly associated with reduced P-delta ( P Δ ) effects, and some codes prescribe fundamental periods below which these effects can be neglected. However, relevant material nonlinearities and different hysteretic responses can highly influence both the amplification of the displacement demand and the limit values of the fundamental period for negligible P Δ effects, at a specific effective height. Considering a large earthquake database, a large variation of the ductility, and several hysteretic models, this paper examines the amplification of the displacement demand due to P Δ effects of short period single-degree-of-freedom (SDOF) systems. It was found that limiting the maximum fundamental period to T 0 = 0 . 4 s for bilinear, to T 0 = 0 . 5 s for Takeda & Sina, and to T 0 = 0 . 6 s for flag-shaped hysteretic systems, the variation of the P Δ displacement amplification with the stability coefficient obtained is, with good approximation, linear. Under these period limitations, simple and accurate analytical estimates of the amplification of the displacement demand have been obtained. For effective heights equal to or larger than h e = 4 m, and ductility levels up to μ = 8, median amplifications of the displacement demand lower than 5% for bilinear, Takeda & Sina, and flag-shaped hysteretic systems required the fundamental period to be limited to T 0 = 0 . 4 s, T 0 = 0 . 8 s, and T 0 = 1 . 0 s, respectively. Highlights: P-delta displacement amplification factors have been examined for a large earthquake database, (7032 ground motion records). The amplification was examined for bilinear, Takeda, Sina and flag-shaped hysteretic systems and different ductility demands. Limit values of the fundamental periods for negligible amplification of the displacement demand have been obtained for each of the hysteretic systems. Simply and accurate analytical estimates have been proposed for the amplification of the displacement demand due to P-delta effects of short-period SDOF systems.